Comparison of the Diagnostic Performance of PI-RADS V1 and PI-RADS V2 for the Detection of Prostate Cancer: A Meta-Analysis - He, Ying; Cong , Ruochen; Zhou, Jie; Xu , Zhenyu; Yang, Jushun; Wang, Lin; Xiao , Jing; He, Bosheng (Urology Journal, 2020)
Purpose: In order to comprehensively determine the diagnostic accuracy of the Prostate Imaging Reporting and Data System version 1 (PI-RADS V1) and PI-RADS version 2 (PI-RADS V2) in prostate cancer (PCa) diagnosis. Materials and Methods: The literatures were screened from the databases, including the Pubmed, Embase, Web of science and Cochrane Library up to January 20th, 2020. The meta-analysis was conducted by Meta-DiSc and quality assessment was performed by using the QUADAS. Furthermore, the sensitivity, specificity, likelihood ratio (LR), diagnostic odds ratio (DOR), as well as receiver operating curve (ROC) related to diagnostic accuracy were pooled. Results: A total of 6 articles containing 814 participants (379 patients) were included in the study. For PI-RADS V1, the combined sensitivity, specificity, PLR, NLR and DOR were 0.82 (95% CI: 0.77-0.85), 0.81 (95% CI: 0.77- 0.85), 4.58 (95% CI: 2.55-8.22), 0.24 (95% CI: 0.18-0.34) and 24.00 (95% CI: 10.38-55.51). With regard to PIRADS V2, the combined sensitivity, specificity, PLR, NLR and DOR were 0.88 (95% CI: 0.84-0.91), 0.81 (95% CI: 0.77-0.84), 4.34 (95% CI: 1.98-9.49), 0.16 (95% CI: 0.08-0.32) and 33.39 (95% CI: 15.05-74.05), respectively. Furthermore, except that the sensitivity of PI-RADS V2 was significantly greater than that of PI-RADS V1 (P = 0.027), there was no remarkably difference in other indicators for the diagnosis of PCa between the two versions. Conclusion: Both PI-RADS V1 and PI-RADS V2 showed good diagnostic performance for PCa diagnosis; moreover, there was no difference in the diagnostic effect between them.